2012
DOI: 10.1186/1471-2288-12-90
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting for under-identification of Aboriginal and/or Torres Strait Islander births in time series produced from birth records: Using record linkage of survey data and administrative data sources

Abstract: BackgroundStatistical time series derived from administrative data sets form key indicators in measuring progress in addressing disadvantage in Aboriginal and Torres Strait Islander populations in Australia. However, inconsistencies in the reporting of Indigenous status can cause difficulties in producing reliable indicators. External data sources, such as survey data, provide a means of assessing the consistency of administrative data and may be used to adjust statistics based on administrative data sources.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Furthermore the allocation of Indigenous status on medical records and registers depends on how, or even if, such information is solicited. This makes research comparing outcomes between Indigenous and non‐Indigenous births an inexact science . Although most persons identifying as Indigenous now live in metropolitan regions, Indigenous status is still associated with social, financial, and educational disadvantages and with rural or remote residence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the allocation of Indigenous status on medical records and registers depends on how, or even if, such information is solicited. This makes research comparing outcomes between Indigenous and non‐Indigenous births an inexact science . Although most persons identifying as Indigenous now live in metropolitan regions, Indigenous status is still associated with social, financial, and educational disadvantages and with rural or remote residence.…”
mentioning
confidence: 99%
“…This makes research comparing outcomes between Indigenous and non-Indigenous births an inexact science. 4,5 Although most persons identifying as Indigenous now live in metropolitan regions, Indigenous status is still associated with social, financial, and educational disadvantages and with rural or remote residence. The proportion of persons identifying as Indigenous is higher in the northern parts of Australia in three jurisdictions: the Northern Territory, Queensland, and Western Australia.…”
mentioning
confidence: 99%
“…Data linkage studies of adult populations have demonstrated that under‐identification of Aboriginal people affects estimates of health, and can overestimate or underestimate the health gap between Aboriginal and non‐Aboriginal Australians . Few studies have examined the identification of Aboriginal children in multiple administrative datasets and how this may affect estimates of health and development …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Data linkage studies of adult populations have demonstrated that underidentification of Aboriginal people affects estimates of health, and can overestimate or underestimate the health gap between Aboriginal and non-Aboriginal Australians. [4][5][6][7][8][9][10] Few studies have examined the identification of Aboriginal children in multiple administrative datasets [11][12][13][14] and how this may affect estimates of health and development. 11,14 A challenge when using administrative data for measuring inequalities in child health and development is that children cannot self-identify.…”
mentioning
confidence: 99%
See 1 more Smart Citation